Manejo de la patología hepatobiliar por radiología intervencional - Palavecino R., Patricio; Niedmann E., Juan Pablo; Cerda B., Fernando; Quevedo P, Claudio; Gutiérrez H., Óscar (Revista Hospital Clínico Universidad de Chile, 2007)
Developing procedures that determine lower associated morbimortality has been medicine tendency of last .years. There is possible with coming of better imaging techniques, together with appearance of better materials have permitted developing more complex procedures, which have been gradually replacing the traditional surgical resolution of many pathologies. Being one of the most important hepatobiliary pathology.